‘Cooking the Meal of Terror’ Manipulative Strategies in Terrorist Discourse: A Critical Discourse Analysis of ISIS Statements - El-Nashar, Mohamed (Terrorism and political violence, 2022)
This paper linguistically investigates terrorist discursive strategies designed to manipulate recipients’ minds into accepting, even embracing, certain ideologies. Though extensive research has been done on manipulative discourse used by journalists and politicians, examining the same discourse used by terrorists received comparatively scant attention. Under Critical Discourse Analysis, we employ a framework of analysis of ISIS discursive tools of manipulation, drawing on Reisigl and Wodak’s (2009) and Wodak’s (2011) discursive strategies, qualitatively and quantitatively analyzing (17) ISIS statements released between 2014 and 2016. We explore the discursive tools ISIS has characteristically used to manipulate its audience and legitimate and defend its actions. The aim is that once terrorist narrative is dissected from a different approach, such effort will be helpful in creating counter-narratives meant to reduce terrorism and vitiate its arguments. Emphasis will be laid on covert vs. overt manipulation, metaphorical dehumanization and metonymic depersonalization. We find that the data contained manipulative tools such as Captatio benevolentiae and volitive modality that are employed to project a positive image about ISIS.